THE ABOUT THE POSSIBILITY OF USING FIBER PREPARATIONS AS A FUNCTIONAL INGREDIENT - L. V. Abushahmanova; L. M. Zakharova (Современная наука и инновации, 2022)
Presented are the results of research of technological properties of beet fiber preparations "Bio-fi Pro WR 400" and "Bio-fi Pro WR 100".